(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
The article deals with theoretical approaches to the formation of historical thinking among schoolchildren in a general educational organization. The article discusses theoretical approaches to the formation of historical thinking among schoolchildren in general education organizations.